Direct synthesis of V-containing all-silica beta-zeolite for efficient one-pot, one-step conversion of carbohydrates into 2, 5-diformylfuran. Issue 24 (20th November 2017) - Zhang, Wei; Hou, Wei; Meng, Tongsuo; Zhuang, Wenxia; Xie, Jingyan; Zhou, Yu; Wang, Jun
Abstract : V-containing all silica beta-zeolite exhibited high atom-efficiency in the direct synthesis of 2, 5-diformylfuran from carbohydrates. Abstract : Vanadium (V)-containing all-silica beta-zeolites (VSi-Beta) were directly synthesized using a dry-gel-conversion route, in which the gel was prepared from the acid-catalysed co-hydrolysis of a silica precursor and ammonium metavanadate. Besides the framework isolated V species, VSi-Beta contained tetrahedral [V2 O7 ] 4− and (VO3 ) n n − species that were bonded to the framework with a high dispersion. These V species resisted the over-oxidation of fructose and efficiently catalyzed the oxidation of 5-hydroxymethylfurfural (HMF) into 2, 5-diformylfuran (DFF). As a result, VSi-Beta demonstrated high activity in the one-pot and one-step conversion of fructose into DFF using atmospheric oxygen (O2 ) in the presence of sulfuric acid, affording a high yield of 86.3% and a maximum turnover number (TON) of 270. The catalyst can be easily recovered by filtration and exhibits good reusability. Various other carbohydrates (glucose, sucrose, inulin, raffinose, maltose and starch) were also effectively converted into DFF using VSi-Beta.